Short-term treatment with taurolidine is associated with liver injury - René Fahrner; Anika Möller; Adrian T. Press; Andreas Kortgen; Michael Kiehntopf; Falk Rauchfuss; Utz Settmacher; Alexander S. Mosig (BMC, 2017)
Abstract Background Taurolidine has been used for peritonitis, oncological and catheter-lock treatment because of its anti-inflammatory properties. It has been suggested that taurolidine has no severe side-effects, but after long-term use morphological and functional changes of the liver were reported. The aim of this study was to investigate the effect of short-term use of taurolidine on the liver. Methods In HepaRG cell cultures and on a novel liver biochip dose-dependent effects of taurolidine treatment on hepatocyte adherence and cell viability was investigated. Furthermore, liver enzymes and interleukin- (IL-) 6 were measured in supernatants. Male rats were treated with low- or high-dose taurolidine, respectively, and compared to controls with physiological saline solution administration regarding blood serum parameters and histology. Results In HepaRG cell cultures, hepatocyte adherence was significantly decreased, cell death and cleaved caspase-3 were significantly increased after administration of taurolidine in a dose-dependent manner. High-dose application of taurolidine led to elevated liver enzymes and IL-6 secretion in hepatic organoid. After 24 h a significant increase of serum GLDH and ASAT was observed in rats treated with high-dose taurolidine treatment. Conclusions Our results suggest that taurolidine caused liver injury after short-term use in in vitro and in vivo models probably due to direct toxic effects on hepatocytes. Therefore, the taurolidine dose should be titrated in further investigations regarding liver injury and inflammation.